Utilization of WhatsApp in English for Islamic Education Learning as a Media of Communication between Lecturers and Students - Al Hamdany, Muhammad Zuljalal (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2022)
WhatsApp is one of the most popular application used by students and lecturers. WhatsApp application gives convenience in interacting and communicating. This research aimed at determining the use of WhatsApp as a medium of communication between lecturers and students in supporting English learning activities at Islamic Education Study Program. The research method applied is quantitative research. The data source is 60 students from IAIN Palopo. This research used the Google form media in survey. The results show that most of the students felt that it was easier for them to communicate and support learning activities compared to other online media. Furthermore, more than 80% of students stated that the application of WhatsApp had a positive impact on their learning activities and supported the improvement of their communication with lecturers. So, WhatsApp is one of the media that has advantages including facilitating communication and supporting learning activities. The ease in using WhatsApp makes students feel helped by this application and becomes one of the important and preferred means of communication for studentsÂ